Association of rs965513 Polymorphism Near FOXE1 Gene with Papillary Thyroid Carcinoma in a sample of Iraqi patients - Alshaikhli, Reyam J.; Alkazaz, Abdulkareem A.; Aljanabi, Abbas A. (Iraqi Journal of Science, 2023)
Thyroid carcinoma incidence is increasing yearly and ranks second among the top ten cancers in Iraq, especially among women. The single nucleotide polymorphism (rs965513, A>C) near FOXE1 gene was found to be associated with papillary thyroid carcinoma risk in several Genome-wide association studies. Therefore, this is a case-control study aimed at identifying whether this variation is associated with the risk of papillary thyroid carcinoma in the Iraqi population. Association of rs965513 was investigated in one hundred and one papillary thyroid carcinoma Iraqi patients and one hundred and two controls using quantitative PCR-high resolution melting technique. The results of genotype and allele frequencies showed that there is a strong association between rs965513 and papillary thyroid carcinoma. The allele C was significantly associated with the disease as a risk factor (P < 0.0003, odd ratio (OR): 2.1014, 95% confidence interval (CI): 1.3987-3.1570), while the allele A represents a protective factor (OR=0.4759). In conclusion, the allele C in rs965513 near FOXE1 gene is strongly associated with papillary thyroid carcinoma in the Iraqi population.